Rebolledo-Gámez, T., & Cárdenas-Rodríguez, R. (Eds.). (2025). Social education: Theories and areas for socio-educational research and intervention. Octaedro - Borge-Moron, Francisco-Jose (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
This review essay undertakes a critical analysis of the work Social Education: theories and scopes for socio-educational research and intervention (Rebolledo-Gámez & Cárdenas-Rodríguez, 2025). The methodology is based on an in-depth review of the book, placing it in dialogue with canonical literature and contemporary debates in Social Pedagogy. The results of the analysis reveal that the work articulates an implicit thesis along four strategic axes: 1) the refounding of professional identity based on ethics and genealogy; 2) the advocacy for the integration of social educators into the formal education system as agents of equity; 3) the adoption of an intersectional approach as a central methodological tool; and 4) the projection of the discipline towards the challenges of global citizenship. The discussion concludes that the book transcends its status as a textbook to become a manifesto that positions Social Education as an indispensable political and pedagogical praxis for the construction of social justice in the 21st century.